Analisis Perbandingan Produktivitas Salak antara Kecamatan Selat dan Kecamatan Bebandem Kabupaten Karangasem - NI PUTU AYU LESTARI DAMAIYANTI; I WAYAN BUDIASA; WIDHIANTINI WIDHIANTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Comparative Analysis of Snake fruit Productivity Between Selat District and Bebandem District Karangasem Regency Indonesia is a country with a fairly potential agricultural sector. The agricultural sector is one of the driving factors for the national economy. Horticultural commodities that are widely developed in Indonesia include fruits, vegetables and various ornamental plants. One of the agricultural commodities in the horticultural sub-sector is snake fruit. The high public demand for horticultural crops, especially snake fruit in Indonesia, requires snake fruit farmers to increase their productivity. Bali Province has a center for the development of snake fruit commodities that applies organic cultivation technology in Karangasem Regency. The Food Crops and Horticulture Department of Karangasem Regency said that Bebandem District is the largest contributor to the production of snake fruit in Bali Province. The research objective was to analyze the productivity of snake fruit farming in Selat District with different productivity of snake fruit farming in Bebandem District, identify the factors that cause the production of snake fruit in the Bebandem District to be different from the Selat District and analyze the development strategy of salak farming in the Selat District. The analysis technique used is the analysis of the Mean Difference Test, the Interpretive Structural Modeling (ISM) and the Descriptive Test. The results showed that Bebandem District had a higher production than Selat District. The future strategy for the development of snake fruit farming in Selat District should focus more on the problem of plant treatment. It is hoped that farmers in Selat District should be able to follow up on the results of the research by doing as much maintenance as possible so that production results can be increased with good quality bark.